Near-field electrospun 3D anisotropic fiber-hydrogel scaffold integrated with photothermal effect for skin wound healing - Ruinan Hao; Hongtao Hu; Xilin Ye; Xiaofeng Chen; Jinzhi Du; Shuolei Li; Chenglin Song; Feng Tian; Nana Zhao; Fujian Xu; Tao Zhang; Feng Rao; et al. (Bioactive Materials)
Wound healing remains a critical clinical challenge due to inflammatory responses, oxidative stress in the wound microenvironment, and impaired tissue remodeling. In this study, an anisotropic scaffold was developed by integrating photothermal stimulation with topographical cues to modulate wound healing. The scaffold consisted of gelatin methacryloyl (GM) hydrogel and radially aligned poly (ε-caprolactone) (PCL) fibers integrated with polydopamine (PDA). The anisotropic scaffold not only exhibited anti-inflammatory effects but also enabled localized thermal stimulation under near-infrared (NIR) light to promote wound healing. It guided cell migration and proliferation from the wound edge toward the center, while the GM hydrogel maintained a moist environment and mitigated uncontrolled thermal damage. In a full-thickness skin wound model in rats, the anisotropic scaffold accelerated wound healing, epidermal regeneration, angiogenesis, and collagen deposition. This approach offers a safe, efficient, and bioactive-factor-free therapeutic strategy for wound repair, showing great potential for clinical translation.